Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Let's solve the given problem step by step for each part.
Given the function:
[tex]\[ q(x) = \frac{1}{x^2 - 9} \][/tex]
### Part (a) [tex]\( q(0) \)[/tex]
To find [tex]\( q(0) \)[/tex]:
[tex]\[ q(0) = \frac{1}{0^2 - 9} = \frac{1}{-9} = -\frac{1}{9} \][/tex]
We have:
[tex]\[ q(0) = -\frac{1}{9} \][/tex]
So, the function value at [tex]\( q(0) \)[/tex] is [tex]\(-\frac{1}{9}\)[/tex].
### Part (b) [tex]\( q(3) \)[/tex]
To find [tex]\( q(3) \)[/tex]:
[tex]\[ q(3) = \frac{1}{3^2 - 9} = \frac{1}{9 - 9} = \frac{1}{0} \][/tex]
Since division by zero is undefined:
[tex]\[ q(3) = \text{UNDEFINED} \][/tex]
So, the function value at [tex]\( q(3) \)[/tex] is UNDEFINED.
### Part (c) [tex]\( q(y+3) \)[/tex]
To find [tex]\( q(y+3) \)[/tex]:
[tex]\[ q(y+3) = \frac{1}{(y+3)^2 - 9} \][/tex]
First, simplify the denominator:
[tex]\[ (y+3)^2 - 9 = y^2 + 6y + 9 - 9 = y^2 + 6y \][/tex]
Now, evaluate [tex]\( q(y+3) \)[/tex] and check specific values, like when [tex]\( y = 3 \)[/tex]:
[tex]\[ \text{For } y + 3 = 6: q(6) = \frac{1}{6^2 - 9} = \frac{1}{36 - 9} = \frac{1}{27} = \frac{1}{27} \][/tex]
Thus:
[tex]\[ q(y+3) = 0.037037037037037035 \text{ (numerically accurate value)} \][/tex]
Therefore, the function value is:
[tex]\[ q(y+3) = 0.037037037037037035 \][/tex]
Given the function:
[tex]\[ q(x) = \frac{1}{x^2 - 9} \][/tex]
### Part (a) [tex]\( q(0) \)[/tex]
To find [tex]\( q(0) \)[/tex]:
[tex]\[ q(0) = \frac{1}{0^2 - 9} = \frac{1}{-9} = -\frac{1}{9} \][/tex]
We have:
[tex]\[ q(0) = -\frac{1}{9} \][/tex]
So, the function value at [tex]\( q(0) \)[/tex] is [tex]\(-\frac{1}{9}\)[/tex].
### Part (b) [tex]\( q(3) \)[/tex]
To find [tex]\( q(3) \)[/tex]:
[tex]\[ q(3) = \frac{1}{3^2 - 9} = \frac{1}{9 - 9} = \frac{1}{0} \][/tex]
Since division by zero is undefined:
[tex]\[ q(3) = \text{UNDEFINED} \][/tex]
So, the function value at [tex]\( q(3) \)[/tex] is UNDEFINED.
### Part (c) [tex]\( q(y+3) \)[/tex]
To find [tex]\( q(y+3) \)[/tex]:
[tex]\[ q(y+3) = \frac{1}{(y+3)^2 - 9} \][/tex]
First, simplify the denominator:
[tex]\[ (y+3)^2 - 9 = y^2 + 6y + 9 - 9 = y^2 + 6y \][/tex]
Now, evaluate [tex]\( q(y+3) \)[/tex] and check specific values, like when [tex]\( y = 3 \)[/tex]:
[tex]\[ \text{For } y + 3 = 6: q(6) = \frac{1}{6^2 - 9} = \frac{1}{36 - 9} = \frac{1}{27} = \frac{1}{27} \][/tex]
Thus:
[tex]\[ q(y+3) = 0.037037037037037035 \text{ (numerically accurate value)} \][/tex]
Therefore, the function value is:
[tex]\[ q(y+3) = 0.037037037037037035 \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.